THE INHIBITORY EFFECT OF DEHYDROEPIANDROSTERONE ON THE ACTIVITY AND ISOENZYME PATTERNS OF LIVER GLUCOSE 6-PHOSPHATE DEHYDROGENASE DURING DIFFERENT STAGES OF GROWTH (Journal of Sciences, Islamic Republic of Iran)
The effect of dehydroepiandrosterone (DHEA) on the activity and isoenzyme patterns of liver glucose 6- phosphate dehydrogenase (G6PD) was investigated in rats during different stages of growth. G6PD activity of mature rats was less than those of the immature (43%) and newborn (35%) animals. DHEA at 10 M) inhibited G6PD activity of the mature , immature and newborn rats by 79%, 39% , and 88% , respectively. Digitonin (0.02%) abolished the inhibitory effect of DHEA in all three groups of rats with an additional22% increase in the enzyme activity in only the mature animals. Gel electrophoresis band patterns of G6PD showed four active bands (I, 11, 111, IV) for the newborn and immature rats. In mature rats band IV was absent but appeared in the presence of digitonin. When electrophoresis was done in the presence of DHEA (10 M) band IV of the immature and neivborn animals disappeared and the activity of band Ifor all animals was partially inhibited with no change in the activities of bands II and III. The data provide further evidence for the possible regulatory role of DHEA on G6PD isoenzyme activities